Thinkwell's public speaking - Alberts, Jess K. (Thinkwell, 2003)
This set of CD ROM lays the foundation for success because, unlike a traditional textbook, students actually like using it. Thinkwell works with the learning styles of students who have found that traditional textbooks are not effective.The CDs have Interactive Exercises with Feedback that test reader's understanding with hundreds of exercises that are automatically graded. The results are available immediately, including fully worked-out solutions and explanations for each exercise. Readers work on the exercises at the computer or print them out to work on later.